Non-Hodgkin’s Lymphoma Breast in a lactating mother : Case Report - Rathee, Neeraj Kumar; Gupta, Nidhi; Sharma, Sawant; Rathee, Hari Krishan (Nepal Journal of Epidemiology, 2022)
Non-Hodgkin’s lymphoma of breast is a rare condition. NHL breast constitute about 0.5% of all malignancies of breast. NHL breast constitute nearly 1% of all cases of NHL. Among all subtypes of NHL, DLBCL (Diffuse large B-cell Lymphoma) is the most common type to be known. Marginal zone lymphoma (10-30%), follicular lymphoma (10-20%) and Burkit Lymphoma (5%) are other common histologic variants. Burkitt lymphoma is mainly seen in pregnant females or lactating females. Breast implant associated anapaestic large cell lymphoma (BIA-ALCL) constitutes remaining case. Thus, primary NHL of Breast is rare condition. DLBCL is most common histologic variant. We report here a rare case of primary NHL Breast. A 30 years old lactating mother came with history of swelling and nipple discharge from bilateral breast. -Treatment approach for low grade NHL breast is Radiotherapy only and for high grade NHL breast there is a role for combined modality approach that is chemotherapy followed by Radiotherapy with or without surgical intervention.